The formation and evolution of the female detective character in literature - Karayeva , Dinara Xaydar qizi (The Lingua Spectrum, 2026)
This article explores the formation and evolution of the female detective character in literature, focusing on how her role has changed from early detective fiction to contemporary works. The study highlights that female characters were initially portrayed as passive figures such as victims or assistants, but gradually evolved into more active and independent investigators. Through qualitative literary analysis of selected texts from different historical periods, including early detective fiction by Edgar Allan Poe, Golden Age works by Agatha Christie, and modern novels such as The Girl with the Dragon Tattoo by Stieg Larsson, the research demonstrates a clear progression in female detective representation. The findings show that modern female detectives, such as Lisbeth Salander, are depicted as complex, professional, and psychologically rich characters, reflecting broader social changes related to gender equality and women’s empowerment. The study concludes that the evolution of female detective characters is closely connected to feminist movements and changing cultural attitudes toward women’s roles in society. Overall, the article contributes to literary and gender studies by providing a structured overview of how female detective characters have developed across different literary periods and highlighting their increasing importance in contemporary fiction.